Phylogeny of HPV-16 and HPV-18 Multiple Infection of a Patient with Cervical Cancer from Dr. Hasan Sadikin General Hospital, Bandung: A Case Report - Vera Amalia Lestari; Ika Agus Rini; Gita Widya Pradini; Edhyana Sahiratmadja; Herman Susanto (The Indonesian Biomedical Journal, 2018)
BACKGROUND: From all of human papillomaviruses (HPV) genotypes capable of causing cervical cancer, it is estimated that 70 percent are HPV-16 and HPV-18. HPV-16 can infect the tissues in single infection or together with other high-risk types of HPV, and the most common is with HPV-18. The origin of HPV can be identified by its phylogenetic tree. The aim of this study was to determine the phylogeny of HPV-16 and HPV-18 multiple infection in cervical cancer, whether both HPVs were from the same origin.METHODS: Cervical tissue biopsies (n=33) were obtained from Hasan Sadikin Hospital in the period of September to November 2016. HPV genotyping test was performed to confirm the HPV-16 and HPV-18 multiple infection. L1 gene of both HPV-16 and HPV-18 were sequenced for phylogenetic analysis.RESULTS: Phylogenetic analysis of L1 HPV-16 and HPV-18 showed the closest relationship with sequence from China and Thailand, respectively.CONCLUSION: HPV-16 and HPV-18 multiple infection of a cervical cancer patient from Dr. Hasan Sadikin General Hospital Bandung showed a very close L1 phylogeny relationship with isolate from Asian region.KEYWORDS: HPV-16, HPV-18, multiple infection, cervical cancer, Bandung